የኢትዮጵያ ኦርቶዶክስ ተዋሕዶ ቤተክርስቲያን ሐዋርያዊ አገልግሎት ከልሳነ ብዙነት አንጻር: የደቡብ ኦሞን እና የጋሙጎፋን አህጉረ ስብከቶች አብነት ያደረገ አጭር የዳሠሣ ጥናት: ዲ/ን ሥዩም ኀይሌ እና ቀሲስ ዶ/ር ሙሉጌታ ሥዩም (Journal-of-Ethiopian-Church-Studies/የኢትዮጵያ-ቤተ-ክርስቲያን-ጥናት-መጽሔት-Live, 2016)
Ethiopia is a country where about 80 languages are spoken and the cultures of different ethnic groups are demonstrated. In this country, the dominant religious institution is the Orthodox Tewahido Church both in terms of history and the number of followers it has. And she is, needless to say, mother and hope to its children. Being the mother of the majority of the population from different linguistic backgrounds, the Church has to pay attention to the languages of the people. This paper, therefore, aims at finding out the degree of attention the Church has paid to the languages of the followers, particularly to the languages found in the Southern Nations, Nationalities, and Peoples of Ethiopia. It also aims to investigate the perception of the Church scholars to the use of native languages at Church, and the challenges it has faced in promoting her mission owing to the language barrier. On top of this, many of the minority languages are believed to have no orthography and hence they do not have written texts. Hence, the study tries to consider the impacts of this in expanding the service of the gospel. The paper also tries to see if there is a mismatch between the number of preachers trained in native languages and the demand for congregations to get service in their mother tongue languages. Once again, the researcher has tried to investigate the endeavor that has been made so far in preparing texts in different languages, and the position of the Church in this regard compared to other religious institutions. Here, the above-mentioned dioceses were taken for this study because many languages are found in this region. And to collect the required data, interviews and observations were used. Accordingly, the result indicates that the Church has not done enough with regard to bringing the minority languages to the Church services. It is also found out that some Church elites perceive local languages as unfit in gospel services, and hence there is a tendency of using Amharic and Ge’ez frequently even if they speak the local languages. This, in turn, has resulted in misunderstanding the message. Some interviewees stated that many people go to the Church but do not understand what is said and hence go back home with no or little understanding of the message. Therefore, the Church has to consider its language use and should be active in translation